2005
DOI: 10.1002/ejic.200400828
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Iridium Complexes with Chiral Dithioether Ligands: Synthesis, Characterisation and Reactivity under Hydrogenation Conditions

Abstract: A series of cationic Ir I complexes containing chiral dithioether ligands have been prepared in order to study the influence of the sulfur substituents and the metallacycle size on the acetamidoacrylate hydrogenation reaction. In the case of complexes 6, 7 and 10, a mixture of diastereomers is observed in solution due to the sulfur inversion processes. In contrast, this fluxional behaviour is efficiently controlled by using bicyclic ligands which inhibit the S-inversion in complexes 8 and 9. The solid-state st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Pd allylic complexes 13 and 14 , coordinated to DEGUS ligands 8 and 9 , respectively, show the presence of four diastereomeric species (at 223 K, relative ratio for 13 , 10/10/10/1; at 243 K, for 14 , 4/3/2/1), which exhibited a fluxional behavior in solution. Results were similar for the Pd 1,3-diphenyl allyl derivative containing ligand 7 8a. This isomeric distribution was in agreement with the two possible absolute configurations at the sulfur atom and the allylic arrangements relative to the ligand backbone ( exo , endo ), assuming free rotation for the N−CH 2 Ph bond.…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…Pd allylic complexes 13 and 14 , coordinated to DEGUS ligands 8 and 9 , respectively, show the presence of four diastereomeric species (at 223 K, relative ratio for 13 , 10/10/10/1; at 243 K, for 14 , 4/3/2/1), which exhibited a fluxional behavior in solution. Results were similar for the Pd 1,3-diphenyl allyl derivative containing ligand 7 8a. This isomeric distribution was in agreement with the two possible absolute configurations at the sulfur atom and the allylic arrangements relative to the ligand backbone ( exo , endo ), assuming free rotation for the N−CH 2 Ph bond.…”
Section: Resultssupporting
confidence: 77%
“…The Pd-chiral dithioether 1 − 12 systems were tested as catalysts in the allylic alkylation of rac - I (Table ). Our preliminary work in the allylic alkylation of rac - I with Pd/ 1 − 12 catalyst precursors showed that the metallacycle size and the nature of the sulfur atom substituent (electronic induction and steric hindrance) influence the activity, but also the selectivity of the process 8a. Pd/type-DIOS systems afforded low conversions (entries 1−3, Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations